Antagonistic Regulation of Cystic Fibrosis Transmembrane Conductance Regulator Cell Surface Expression by Protein Kinases WNK4 and Spleen Tyrosine Kinase - Mendes, Ana Isabel (2011)
Members of the WNK (with-no-lysine [K]) subfamily of protein kinases regulate various ion channels involved in sodium, potassium, and chloride homeostasis by either inducing their phosphorylation or regulating the number of channel proteins expressed at the cell surface. Here, we describe findings demonstrating that the cell surface expression of the cystic fibrosis transmembrane conductance regulator (CFTR) is also regulated by WNK4 in mammalian cells. This effect of WNK4 is independent of the presence of kinase and involves interaction with and inhibition of spleen tyrosine kinase (Syk), which phosphorylates Tyr512 in the first nucleotide-binding domain 1 (NBD1) of CFTR. Transfection of catalytically active Syk into CFTR-expressing baby hamster kidney cells reduces the cell surface expression of CFTR, whereas that of WNK4 promotes it. This is shown by biotinylation of cell surface proteins, immunofluorescence microscopy, and functional efflux assays. Mutation of Tyr512 to either glutamic acid or phenylalanine is sufficient to alter CFTR surface levels. In human airway epithelial cells, downregulation of endogenous Syk and WNK4 confirms their roles as physiologic regulators of CFTR surface expression. Together, our results show that Tyr512 phosphorylation is a novel signal regulating the prevalence of CFTR at the cell surface and that WNK4 and Syk perform an antagonistic role in this process.